2013
DOI: 10.4103/0301-4738.112164
|View full text |Cite
|
Sign up to set email alerts
|

A case of Churg-Strauss syndrome and central retinal artery occlusion with good visual recovery

Abstract: Here we report a case of Churg–Strauss syndrome (CSS) and central retinal artery occlusion (CRAO), with good visual recovery. A 58-year-old Japanese man with CSS experienced acute painless loss of vision in his right eye. CRAO was diagnosed by fundoscopic findings (retinal whitening with a cherry-red spot). Steroid pulse therapy (methylprednisolone at 1 g daily for 3 days) followed by combined treatment with prednisolone (30 mg/day) and cyclophosphamide (150 mg/day) was administered; his visual acuity recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…When ANCA-associated vasculitis is complicated by eye symptoms, therapeutic intervention with steroids is generally considered necessary. [ 30 ] Although the prognosis of CRAO due to ANCA-associated vasculitis is generally considered to be poor, early therapeutic intervention may result in the recovery of a relatively favorable VA. [ 18 ] In our patient, the improvement of VA might have been due to the fact that steroid semi-pulse therapy was also initiated soon after she became aware of the sudden decreased of VA. Hence, and as our findings indicate, in patients with CRAO associated with general symptoms, it is important to perform detailed physical examinations, including a blood test, as needed, in order to identify the cause, and to start treatment early, while keeping the possibility of conditions secondary to ANCA-associated vasculitis in mind.…”
Section: Discussionmentioning
confidence: 89%
“…When ANCA-associated vasculitis is complicated by eye symptoms, therapeutic intervention with steroids is generally considered necessary. [ 30 ] Although the prognosis of CRAO due to ANCA-associated vasculitis is generally considered to be poor, early therapeutic intervention may result in the recovery of a relatively favorable VA. [ 18 ] In our patient, the improvement of VA might have been due to the fact that steroid semi-pulse therapy was also initiated soon after she became aware of the sudden decreased of VA. Hence, and as our findings indicate, in patients with CRAO associated with general symptoms, it is important to perform detailed physical examinations, including a blood test, as needed, in order to identify the cause, and to start treatment early, while keeping the possibility of conditions secondary to ANCA-associated vasculitis in mind.…”
Section: Discussionmentioning
confidence: 89%
“…1,4 Early initiation of pulse-dose steroids may improve visual outcomes. Kamata et al 6 reported a case of antineutrophil cytoplasmic antibody-negative CRAO in a patient with eosinophilic granulomatosis with polyangiitis who had good visual recovery to 20/30 after initiation of pulse ster oid therapy. Reddy et al 3 reported 2 cases of eosinophilic granulomatosis with polyangiitis following amaurosis fugax.…”
Section: Discussionmentioning
confidence: 99%
“…As in the other diseases of this group, conjunctivitis, episcleritis, scleritis, and PUK are the more common manifestations of eosinophilic GPA [77]. Amaurosis fugax, retinal artery occlusions, ischemic optic neuropathy, dacryoadenitis, and orbital inflammation have been described [78][79][80][81][82][83].…”
Section: Microscopic Polyangiitis This Subtype Characteristically Pre...mentioning
confidence: 99%